Los pliegues de la barrera de guataquí - girardot: ¿producto de un despegue de la cobertera cretácica de la cordillera oriental? (1995)
In this paper the folds of the so - called barrier of Guataquí - Girardot are interpreted as detachment folds. In a first step, depths of a décollement horizon are calculated, using the classical excess - area method. These results are discussed in the light of a defonnational scenario, which includes 1) uplift of the internal parts of the Eastern Cordillera and 2) a gravity - driven gliding of the Cretaceous cover toward its bordering depressions, giving rise to a partial tectonic denudation. It is concluded that, with respect to this scenario and in order to carry out a satisfactory retro - defonnation by balanced areas, distributed shear and internal defonnation should be allowed for as further parameter in the decollement calculations.